Ethanol sensing evaluation of sol–gel barium calcium ferrite. Issue 11 (15th August 2016) - Sen, Shrabanee; Anand, Pravita; Narjinary, M.; Mursalin, S.K. Md; Manna, R.
Abstract: Hexaferrites are very attractive materials for high-frequency circuits and operating devices, nevertheless their use for sensing application is very rare. In the present work, BaCa2 Fe16 O27 hexaferrite was synthesized by a simple sol–gel technique. Structural and microstructural information have been obtained by X-ray powder diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The gas sensing performance of BaCa2 Fe16 O27 hexaferrite-based sensors was investigated for the detection of some common volatile organic compounds and gases like ethanol, acetone, methane and carbon monoxide. The results showed the sensors to exhibit high sensitivity, quick response/recovery and good reproducibility and stability towards 100 ppm ethanol. Moreover the sensors proved to be highly selective from measurements of cross sensitivity.